A carbon footprint simulation model for the cork oak sector - Demertzi, Martha (2020)
In the present study, a simulation model for the calculation of the carbon footprint of the cork oak sector (CCFM) is developed for the first time. A life cycle approach is adopted including the forest management, manufacturing, use and end-of-life stages. CCFM allows the user to insert the cork type used as raw material and its respective quantity and the distances in-between the various stages. The user can choose among different end-of-life destination options for the used cork products. The option of inserting different inputs, allows the use of the present simulation model for different cork oak systems, in different countries and with different conditions. CCFM allows the identification of the stages and products with the greatest carbon footprint and thus, a better management of the sector from an environmental perspective. The Portuguese cork oak sector is used as an application example of the model. The results obtained showed that the agglomeration industry is the hotspot for the carbon footprint of the cork sector mainly due to the production of the resins that are mixed with the cork granules for the production of agglomerated cork products. The consideration of the biogenic carbon emissions and sequestration of carbon at the forest in the carbon footprint, resulted to a great decrease of the sector's carbon footprint. Future actions for improvement are suggested in order to decrease the carbon footprint of the entire cork sector. It was found that by decreasing by 10% the emission factor of the agglomeration and transformation industries, substituting the transport trucks by more recent ones and by decreasing by 10% the cork products reaching the landfilling end-of-life destinations (while increasing the quantities reaching incineration and recycling), a decrease of the total CF (excluding the biogenic emissions and sequestration) of the entire cork industry by 10% can be achieved.